Synthesis and Evaluation of 1, 8‐Disubstituted‐Cyclam/Naphthalimide Conjugates as Probes for Metal Ions. Issue 4 (3rd August 2016) - Wong, Joseph K.‐H.; Ast, Sandra; Yu, Mingfeng; Flehr, Roman; Counsell, Andrew J.; Turner, Peter; Crisologo, Patrick; Todd, Matthew H.; Rutledge, Peter J.
Abstract: Fluorescent molecular probes for metal ions have a raft of potential applications in chemistry and biomedicine. We report the synthesis and photophysical characterisation of 1, 8‐disubstituted‐cyclam/naphthalimide conjugates and their zinc complexes. An efficient synthesis of 1, 8‐bis‐(2‐azidoethyl)cyclam has been developed and used to prepare 1, 8‐disubstituted triazolyl‐cyclam systems, in which the pendant group is connected to triazole C4. UV/Vis and fluorescence emission spectra, zinc binding experiments, fluorescence quantum yield and lifetime measurements and pH titrations of the resultant bis‐naphthalimide ligand elucidate a complex pattern of photophysical behaviour. Important differences arise from the inclusion of two fluorophores in the one probe and from the variation of triazole substitution pattern (dye at C4 vs. N1). Introducing a second fluorophore greatly extends fluorescence lifetimes, whereas the altered substitution pattern at the cyclam amines exerts a major influence on fluorescence output and metal binding. Crystal structures of two key zinc complexes evidence variations in triazole coordination that mirror the solution‐phase behaviour of these systems. Abstract : I‐on the prize : Fluorescent molecular probes have many applications in chemistry and biomedicine. Combining naphthalimide reporters with macrocyclic cyclam ligands, zinc‐responsive probes have been built by using a new 1, 8‐disubstituted‐cyclam‐azide derivative and click chemistry. The fluorescence response of these systems changes significantly with small alterations of ligand connectivity, and shows intriguing variation with solvent polarity. Crystal structures shed further light on the situation.